Comprehensive traditional East Asian medicine treatment strategy for obesity considering the therapeutic effects and adverse events: A protocol for systematic review and network meta-analysis. Issue 6 (11th February 2022) - Chu, Hongmin; Kang, Byungsoo; Youn, Bo-Young; Kim, Kwan-il; Park, Jinbong; Leem, Jungtae
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Obesity has become a serious global health problem due to its increasing prevalence. Because of several limitations or adverse events associated with conventional western medicine therapies, there has been an increase in demand for alternative therapies such as traditional East Asian medicine (TEAM). This study aims to provide comprehensive evidence-based information assessing the clinical efficacy and safety of TEAM treatment for obesity as the basis for reliable clinical strategies for patients with obesity. Methods: Electronic searches of the PubMed, Cochrane Library, EMBASE, China National Knowledge Infrastructure, OASIS, and Korea Citation Index will be performed. Methodological quality will be assessed using the "risk of bias" tool. The primary outcome for efficacy will be weight loss. The secondary outcomes will be response rate, body mass index, waist circumference, and blood pressure. We will also evaluate the rates of adverse events and mortality for safety assessment. First, we will conduct a conventional pairwise meta-analysis. Next, we will conduct network meta-analysis using the frequentist approach. We shall verify the assumption of network meta-analysis and provide network geometry, P-score, net league table, and intervention-based forest plot. A subgroup analysis will be conducted to ascertain the factors that affect treatment, such as dosage, treatment duration, and severity of obesity. Results: The results of this study will provide high-quality systematic reviews that can assist decision making in obesity management. Our network meta-analysis results can provide direct and indirect comparison evidence on comparative efficacy and safety. Conclusion: This study will provide fundamental data for prospective research on the application of TEAM in patients with obesity. Protocol registry number of online registry: This study protocol was registered in open Science framework (OSF) (Registration DOI: 10.17605/OSF.IO/ETWDS) URL of the online registry: https://osf.io/etwds .